New paleopteran and polyneopteran insects from the Carboniferous of Northern France - Mathieu Boderau; Patrick Roques; Andre Nel (Acta Palaeontologica Polonica)
Two paleopteran and four polyneopteran insects are described from the Moscovian, Pennsylvanian, of coal slag heaps of Avion and Bruay-la-Bussière, Pas-de-Calais, Northern France, namely the spilapterid paleodictyopteran Spilaptera sp., Megasecoptera indet., a new caloneurodean Fusiogramma minuta gen. et sp. nov., an Archaeorthoptera indet., a new paoliid Avionpaolia amansfossilia gen. et sp. nov., and a Paoliida gen. et sp. indet. These new taxa confirm the important paleodiversity of the late Carboniferous insect assemblage from this area. Small insects are especially diverse and abundant in materials from Avion. Unfortunately, these coal slag heaps are now closed. We postulate that more efficient policy of field research should be applied to save the important insect assemblages of the area.